The immunomodulatory effects of GLP-1 receptor agonists in neurogenerative diseases and ischemic stroke treatment - Sun, Haohui; Hao, Yue; Liu, Hao; Gao, Feng (Frontiers in Immunology, 2025)
Glucagon-like peptide-1 (GLP-1) receptor is widely distributed in the digestive system, cardiovascular system, adipose tissue and central nervous system. Numerous GLP-1 receptor-targeting drugs have been investigated in clinical studies for various indications, including type 2 diabetes and obesity (accounts for 70% of the total studies), non-alcoholic steatohepatitis, Alzheimer's disease, and Parkinson's disease. This review presented fundamental information regarding two categories of GLP-1 receptor agonists (GLP-1RAs): peptide-based and small molecule compounds, and elaborated their potential neuroprotective effects by inhibiting neuroinflammation, reducing neuronal apoptosis, and ultimately improving cognitive function in various neurodegenerative diseases. As a new hypoglycemic drug, GLP-1RA has a unique role in reducing the concurrent risk of stroke in T2D patients. Given the infiltration of various peripheral immune cells into brain tissue, particularly in the areas surrounding the infarct lesion, we further investigated the potential immune regulatory mechanisms. GLP-1RA could not only facilitate the M2 polarization of microglia through both direct and indirect pathways, but also modulate the quantity and function of T cell subtypes, including CD4, CD8, and regulatory T cells, resulting into the inhibition of inflammatory responses and the promotion of neuronal regeneration through interleukin-10 secretion. Therefore, we believe that the "Tregs-microglia-neuron/neural precursor cells" axis is instrumental in mediating immune suppression and neuroprotection in the context of ischemic stroke. Given the benefits of rapid diffusion, favorable blood-brain barrier permeability and versatile administration routes, these small molecule compounds will be one of the important candidates of GLP-1RA. We look forward to the further clinical evidence of small molecule GLP-1RA intervention in ischemic stroke or T2D complicated by ischemic stroke.